Colonization potential of endophytes from halophytic plants growing in the “Runn of Kutch” salt marshes and their contribution to mitigating salt stress in tomato cultivation - Sahu, Pramod K.; Shafi, Zaryab; Singh, Shailendra; Ojha, Khushboo; Jayalakshmi, K.; Tilgam, Jyotsana; Manzar, Nazia; Sharma, Pawan K.; Srivastava, Alok K. (Frontiers in Microbiology, 2023)
Increasing soil salinity depreciates the quantity of the crop produce. Looking at the tremendous potential of plant-associated microorganisms in salinity stress mitigation, it would be very useful in exploring and deciphering salt-tolerant microorganisms from halophytic plants and their utilization in cultivated plants. With this aim, in the present study, four halophytic plants were taken from Rann of Kutch, and bacterial endophytes were isolated from different plant organs. These endophytes were characterized by plant growth and health promotion features. The molecular identification was done based on 16s rRNA sequence similarity. It was found that the endophytic bacteria isolated from 4 different halophytes found sharing phylogenetic relatedness. Four potential endophytes Alkalihalobacillus gibsonii 2H2, Achromobacter insuavis 2H18, Terribacillus halophilus 2H20, and Bacillus siamensis 4H1 were tested in tomato for salinity stress alleviation. Changes in the levels of antioxidants were analyzed. Total chlorophyll, total phenolics, malondialdehyde, and proline content indicated reduced damage in the plant system due to salinity by the application of endophytes. All the treatments exhibited low levels of electrolyte leakage. The accumulation of enzymatic reactive oxygen species scavengers was assessed from the levels of peroxidase, catalase, superoxide dismutase, phenylalanine ammonia-lyase, ascorbate peroxidase, and guiacol peroxidase. The NBT and DAB staining confirmed the findings. The reduction in the accumulation of Na+ ions in tomato leaves was visualized using Sodium Green probes under CSLM and found to be lowest in Terribacillus halophilus 2H20 and Bacillus siamensis 4H1 inoculated plants. The endophyte Terribacillus halophilus 2H20 was the most promising isolate. The colonization in tomato roots was confirmed using a cell tracker system. Results showed that the endophytes were found to have salinity stress mitigation traits. The efficiency could be further improved with the combination of other endophytes tested earlier.